Cover Picture: Catalytic Hydrodeoxygenation of High Carbon Furylmethanes to Renewable Jet‐fuel Ranged Alkanes over a Rhenium‐Modified Iridium Catalyst (ChemSusChem 16/2017). Issue 16 (16th August 2017) - Liu, Sibao; Dutta, Saikat; Zheng, Weiqing; Gould, Nicholas S.; Cheng, Ziwei; Xu, Bingjun; Saha, Basudeb; Vlachos, Dionisios G.
Abstract : The Cover picture shows the use of renewable aviation fuels produced from C−C coupling and hydrodeoxygenation of lignocellulosic biomass‐derived platform molecules. Production of these molecules occurs through an energy efficient process using a bifunctional Ir−ReO x /SiO2 catalyst and yields up to 99% branched chain alkanes at low temperature. The high efficiency and high products selectivity eliminate the need for complex separations and may render bio‐based aviation fuels to become cost‐competitive and sustainable. More details can be found in the Full Paper by Liu et al. onpage 3225 in Issue 16, 2017 (DOI:10.1002/cssc.201700863 ).